Kepemimpinan dan Komunikasi Efektif Sebagai Prediktor Positif dari Budaya Keselamatan Pasien - Rahadian Alif; Agusta Dian Ellina; Joko Prasetyo (FORIKES, 2024)
Health centers are required to implement patient safety programs in all their activities. Therefore, a patient safety culture must be created and developed by health centers. Building a patient safety culture requires leadership roles and effective communication. This study aimed to analyze the influence of leadership roles and effective communication on patient safety culture in inpatient health centers in Kediri Regency. The design of this study was cross-sectional, involving 140 midwives and nurses of inpatient health centers in Kediri Regency, who were selected using purposive sampling techniques. Data collection was carried out using questionnaires and data analysis was carried out using multiple linear regression tests. The results of the F test showed a p value = 0.000, which means that leadership roles and effective communication simultaneously influenced patient safety culture. The results of the t test produced a p value = 0.000 for the leadership role, so this factor influences patient safety culture. For the effective communication factor, the p value = 0.001, which means that effective communication influenced patient safety culture. In conclusion, leadership roles and effective communication are positive predictors of patient safety culture in inpatient health centers in Kediri Regency.Keywords: patient safety culture; leadership roles; effective communication ABSTRAK Puskesmas berkewajiban untuk melaksanakan program keselamatan pasien dalam setiap kegiatannya. Oleh karena itu, budaya keselamatan pasien harus diciptakan dan dikembangkan oleh puskesmas. Membangun budaya keselamatan pasien memerlukan peran kepemimpinan dan komunikasi yang efektif. Penelitian ini bertujuan untuk menganalisis pengaruh peran kepemimpinan dan komunikasi efektif terhadap budaya keselamatan pasien di puskesmas rawat inap Kabupaten Kediri. Rancangan penelitian ini adalah cross-sectional, dengan melibatkan 140 bidan dan perawat puskesmas rawat inap Kabupaten Kediri, yang dipilih dengan teknik purposive sampling. Pengumpulan data dilakukan menggunakan kuesioner dan analisis data dilakukan menggunakan uji regresi linier berganda. Hasil uji F menunjukkan nilai p = 0,000, yang berarti bahwa peran kepemimpinan dan komunikasi efektif berpengaruh secara simultan terhadap budaya keselamatan pasien. Hasil uji t menghasilkan nilai p = 0,000 untuk peran kepemimpinan, sehingga faktor ini berpengaruh terhadap budaya keselamatan pasien. Untuk faktor komunikasi efektif, nilai p = 0,001, yang berarti bahwa komunikasi efektif juga berpengaruh terhadap budaya keselamatan pasien. Sebagai kesimpulan, peran kepemimpinan dan komunikasi efektif merupakan prediktor positif dari budaya keselamatan pasien di puskesmas rawat inap Kabupaten Kediri.Kata kunci: budaya keselamatan pasien; peran kepemimpinan; komunikasi efektif